2019
DOI: 10.1021/acs.orglett.9b01399
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Indole Structure on Pyrroloindolines via AgNTf2-Mediated Amination/Cyclization Cascade: Application to Total Synthesis of (+)-Pestalazine B

Abstract: An N-linked indole structure was constructed on the 3a-position of pyrroloindoline derivatives via a cascade process involving silver-mediated amination of bromopyrroloindolines with 2-ethynylanilines with subsequent 5-endo-dig cyclization. In this reaction, AgNTf2 was used as a tandem reagent, which activated the bromo group as a σ-Lewis acid and the alkyne moiety as a π-Lewis acid. Switching from the initial step to the second step was conducted by controlling the temperature. This protocol was applied to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Rh(III)/[RhCp*Cl 2 ] 2 catalyzed stepwise dimerization of 2alkylanilines 11 and 12 (Scheme 4) [14] to the corresponding condensed indolo[3,2-c] quinolines 13 in HFIP solvent at 120°C under aerobic conditions has been described by Xinyang Zhang et al [15] The replacement of HFIP with other solvents such as toluene, DCE and MeOH gave very poor yield of the desired indole derivative. In addition to this other catalyst such as Pd(OAc) 2 , RuCl 3 and InBr 3 also provided only trace amount of the product.…”
Section: Rhodium-catalysed Synthesis Of Indolesmentioning
confidence: 99%
See 2 more Smart Citations
“…Rh(III)/[RhCp*Cl 2 ] 2 catalyzed stepwise dimerization of 2alkylanilines 11 and 12 (Scheme 4) [14] to the corresponding condensed indolo[3,2-c] quinolines 13 in HFIP solvent at 120°C under aerobic conditions has been described by Xinyang Zhang et al [15] The replacement of HFIP with other solvents such as toluene, DCE and MeOH gave very poor yield of the desired indole derivative. In addition to this other catalyst such as Pd(OAc) 2 , RuCl 3 and InBr 3 also provided only trace amount of the product.…”
Section: Rhodium-catalysed Synthesis Of Indolesmentioning
confidence: 99%
“…Hidetoshi Tokuyama et al [15] have reported cascade process for construction of N-linked indoles 108 (scheme 36) on 3aposition of pyrroloindoline 105. [56] In this process Bromopyrroloindoline 105 undergo silver catalysed one-pot amination with 2-ethynyl anilines 106 through 5-endo-dig cyclization in the presense of DTPB as an oxidant in dichloromethane solvent.…”
Section: Silver-catalysed Synthesis Of Indolesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the established AgNTf 2 -mediated substitution reaction of bromopyrroloindole proved to be effective for various aromatic compounds, including heterocycles. 81,82) Having established an efficient method for introducing an indolyl group to a pyrroloindole nucleus using AgNTf 2mediated nucleophilic substitution, we started synthetic stud-ies aimed at the total synthesis of T988 A-C (70-72). The synthesis commenced with the condensation of L-tryptophan methyl ester hydrochloride (89) and D-serine derivative 90 (Fig.…”
Section: Total Synthesis Of T988smentioning
confidence: 99%
“…Subsequently, You’s group achieved an elegant work of regio- and enantioselective synthesis of N -allyl 2-arylindoles via one-pot iridium-catalyzed allylic amination/transition-metal-catalyzed cyclization reactions (Scheme , path b) . Very recently, Tokuyama and co-workers reported the silver-mediated amination of bromopyrroloindolines with 2-ethynylanilines with subsequent 5-endo-dig cyclization for constructing an N-linked indole segment at the 3-position of pyrroloindoline, in which AgNTf 2 plays a dual role in the activation of both a bromo group and an alkyne moiety (Scheme , path c) . Notably, the group of Wang and Lv first realized a cheap copper-catalyzed coupling/cyclization reaction of 2-alkynylanilines and boronic acids for the one-pot access to N -alkyl 2-arylindoles, albeit with a low efficiency and limited structural scope (Scheme , path d) .…”
Section: Introductionmentioning
confidence: 99%